The immunomodulatory effect of probiotics beyond atopy: an update. (April 2014) - Vitaliti, Giovanna; Pavone, Piero; Guglielmo, Francesco; Spataro, Giuseppina; Falsaperla, Raffaele
Abstract Background: In the past decades, the theory of "allergen avoidance" was considered the standard treatment for preventing the onset of allergic diseases. Recently, the concept of "immune tolerance" has replaced this old theory, and induction of tolerance by exposure is actually considered the appropriate method for preventing atopic diseases and other immunomediated pathologies. On the other hand, it is obvious that for public health reasons, abandoning current medical and hygienic practices is not desirable; therefore, safe alternatives, such as probiotics, have been suggested for providing necessary microbial stimulation. Objective: The purpose of our review is to describe the immunomodulatory and anti-inflammatory properties of probiotics, reporting literature data on their effect when used for the treatment of immunomediated diseases. Materials and methods: Articles reporting the evidence on the use of probiotics in immunomediated diseases, such as atopy, cow's milk allergy and rheumatoid arthritis (RA), and in inflammatory diseases, such as inflammatory bowel diseases (IBDs), with or without statistical meta-analysis, were selected in three different search engines: (1) MEDLINE via PubMed interface, (2) Scopus and (3) Google Scholar for all articles published from inception to July 2013. Titles and abstracts of identified papers were screened by two independent reviewers to determine whether they met the eligibility criteria of interest to develop our review. Subsequently, full texts of the remaining articles were independently retrieved for eligibility by the two reviewers. Results and Discussion: The recent literature is focusing its interest towards the immunologic properties of relatively harmless organisms, including lactobacilli and bifidobacteria, helminths and saprophytic mycobacteria that may skew immune responses towards immunoregulation by inducing Treg cells, rather than eliciting a pro-inflammatory immune response. For this reason, recent researches have been addressed on the use of probiotics to promote immunoregulation in atopic diseases, such as atopic/eczema dermatitis syndrome and food allergy, as well as in inflammatory-based diseases such as IBDs, RA and bronchial asthma.